Characteristics of patients returning to emergency departments in Naples, Italy - Marinelli Paolo; Albano Luciana; Abbate Rossella; Di Giuseppe Gabriella; Angelillo Italo F (BMC, 2008)
Abstract Background Crowding in hospital Emergency Departments (EDs) is a problem in several countries. We evaluated the number and characteristics of patients who make repeated visits to the EDs in Naples, Italy. Methods All patients (≥ 16 years) who presented to the EDs of three randomly selected non-academic acute care public hospitals, within randomly selected week periods, were studied. The two outcomes of interest were the re-utilization, within 72 hours, of the ED and the number of visits in the previous year. Results Of the 1430 sampled patients, 51.9% self-reported multiple visits in the previous year and 10.9% and 1.6% used the ED for 3 and ≥4 times, respectively. The number of visits in the previous year was significantly higher in those who live closer to hospital, with a more severe burden of overall comorbidity, and who were on pharmacological treatment. Overall, 72-hours return visits were found in 215 patients (15.8%). Patients were more likely to re-use within 72 hours the ED if younger, were not on pharmacological treatment, attended the ED more times in the previous year, were referred by a physician, arrived at the ED by car driven by other person, had problems of longer duration prior to arrival at the ED, had a surgical ED discharge diagnosis, and were admitted to the hospital. Conclusion The data may assist policymakers in the development and implementation of protocols to track changes in the re-utilization of the ED for the high financial impact and for the benefit of the patients.